A temperature-independent prediction model predicts the vapor-liquid equilibrium of CO2-based binary mixtures. (August 2022) - Wu, Zirui; Shi, Lingfeng; Sun, Rui; Tian, Hua; Wang, Xuan; Hu, Peng; Shu, Gequn
Highlights: The model is proposed to predict the vapor-liquid equilibrium of CO2 -based binary mixtures. The biggest advantage of the model proposed in this work is that there are no fitting parameters. The AARD p, AAD y 1, and AARD αij are 2.23%, 0.0095 and 5.21%. By testing the CO2 +R116 and CO2 +R610, we can obtain that the model has sure universality. Abstract: CO2 -based binary mixtures are considered good alternative working fluids in the refrigeration and power cycle due to their excellent performance and environmental friendliness. The vapor-liquid phase equilibrium of CO2 -based binary mixtures is the basis for calculating mixing enthalpy and heat capacity, which is essential for thermodynamic analysis. In this work, based on the vdW mixing rules, we proposed a kij model ( kij = θj ki - θi kj ). In the proposed model, ki and kj are defined as pure interaction factors of the pure components, θj is the influence factor of component j to component i, and θi is the influence factor of component i to component j . After continuous fitting and trial calculation, we developed a semi-empirical formula, which is called a temperature-independent prediction model. The model does not have any adjustable parameters, which are only related to the physical properties (critical pressure (kPa), critical temperature (K), and acentric factor) and molecular structure (carbon-carbon double bonds, carbon-fluorine, chlorine, iodine, and oxygen atoms) of the components. The temperature-independent prediction model can predict the bubble-point pressures, vapor phase molar fractions, and relative volatilities very well, which is better than the prediction model based on the vdW mixing rules by others and the group contribution model based on the excess free energy ( G E ) mixing rules (PR+MHV1+UNIFAC). The total average absolute relative deviation of pressures, the total average absolute deviation of vapor phase molar fractions, and the total average absolute relative deviation of relative volatilities by the temperature-independent prediction model are 2.23%, 0.0095, and 5.21%, respectively.